Instructive manual and teacher's guide to english teaching at Guaca Arriba Elementary School - Loo M., Evans Enrique; Morales Martínez, Wheslly P.; Serrano de Lezcano, Leydiana; De Gracia, Edward; Vargas, Victor (David, Panamá : UDELAS, 2011)
We decided to elaborate a student manual and teacher's guide according with their english knowledge level as an important tools that will help the teacher and students since 2011.
INDEX Dedication Scknowledgment Index Vision and Mision Introduction Chapter I Referencial framework the project Chapter II Proposal description Expected result Action activities Action lines Activities Activities description Methodologies to implement Guide and instruments Activities schedule Organization chart Human resources Material resources Financial resources Evaluation Conclusion Recommendation Bibliography Annex
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- PROYECTO COMUNITARIO DE LICENCIATURA; FACULTAD DE EDUCACIÓN; ESCUELA DE INGLÉS; LICENCIATURA DE DOCENCIA EN INGLÉS; GUACA ARRIBA ELEMENTARY SCHOOL - CHRIQUÍ